2013
DOI: 10.4103/0974-2700.115320
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of patients that experience cardiopulmonary arrest following aortic dissection and aneurysm

Abstract: Aim:The aim of this study is to investigate the characteristics of patients experience cardiopulmonary arrest (CPA) in the acute phase following aortic dissection and aneurysm (AD).Materials and Methods:Patients who were transported to this department from January 2005 to December 2010 and subsequently diagnosed with AD were included in this study. Patients with asymptomatic AD or those with AD that did not develop CPA were excluded. The AD was classified into four categories: Stanford A (SA), Stanford B (SB),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Kurimoto et al 31 reported that one patient with out-of-hospital CPA after ROSC underwent aortic repair and survived without neurological sequelae. Yanagawa et al 32 reported that the survival rate among 24 patients with CPA at presentation caused by ATAAD was 13%, and only one patient underwent surgical treatment. Given recent advances in rapid medical transportation and early diagnosis system using echocardiography and CT, and the introduction of extracorporeal cardiopulmonary resuscitation (ECPR) using extracorporeal membrane oxygenation (ECMO), the number of ATAAD patients with CPA has been increasing.…”
Section: Epidemiology and Clinical Presentationmentioning
confidence: 99%
“…Kurimoto et al 31 reported that one patient with out-of-hospital CPA after ROSC underwent aortic repair and survived without neurological sequelae. Yanagawa et al 32 reported that the survival rate among 24 patients with CPA at presentation caused by ATAAD was 13%, and only one patient underwent surgical treatment. Given recent advances in rapid medical transportation and early diagnosis system using echocardiography and CT, and the introduction of extracorporeal cardiopulmonary resuscitation (ECPR) using extracorporeal membrane oxygenation (ECMO), the number of ATAAD patients with CPA has been increasing.…”
Section: Epidemiology and Clinical Presentationmentioning
confidence: 99%
“…However, AD can be painless and lead to various symptoms, such as hoarseness, heart failure, syncope, stroke, paraplegia, anuria, or sudden death. 1,2 We, herein, present the case of a patient with acute aortic dissection Type A whose initial complaint was focal convulsion.…”
Section: Introductionmentioning
confidence: 99%